Positive electrode active material, its manufacturing method, positive electrode and lithium secondary battery including the same

JP2025500564AActive Publication Date: 2025-01-09LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024539061
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-07
Filing Date
2023-01-06
Publication Date
2025-01-09
Estimated Expiration
2043-01-06

AI Technical Summary

Benefits of technology

【0013】 本発明に係る正極活物質は、粒子強度の高い単粒子又は準単粒子形態のリチウムニッケル系酸化物を含み、電極の製造及び充放電時に粒子割れが少なく、電解液との接触面積が少ないので、電解液との副反応の発生が抑制されるので、二次電池の適用時にガス発生量が少なく、高温寿命特性に優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500564000001_ABST
    Figure 2025500564000001_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium nickel-based oxide in the form of a quasi-single particle, which is a single particle consisting of one nodule or a composite of 30 or less nodules; and a positive electrode active material which includes a coating portion containing Co and is formed in an island shape on a part of the surface of the lithium nickel-based oxide particle, and in a Ni L3-edge spectrum obtained by measuring the surface of the lithium nickel-based oxide in contact with the coating portion by electron energy loss spectroscopy, the intensity at 855.5 eV is greater than the intensity at 853 eV, a manufacturing method thereof, and a positive electrode and a lithium secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0002995, filed on January 7, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material, a manufacturing method thereof, and a positive electrode and a lithium secondary battery including the same, and more particularly to a positive electrode active material in a single particle or quasi-single particle form having excellent life characteristics and resistance characteristics, a manufacturing method thereof, and a positive electrode and a lithium secondary battery including the same. [Background technology]

[0003] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.

[0004] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as the positive electrode active material of lithium secondary batteries. Among them, lithium cobalt oxide has the advantage of high operating voltage and excellent capacity characteristics, but the raw material cobalt is expensive and the supply is unstable, making it difficult to commercially apply to large-capacity batteries. Lithium nickel oxide has low structural stability and is difficult to realize sufficient life characteristics. On the other hand, lithium manganese oxide has excellent stability but has a problem of low capacity characteristics. Therefore, lithium composite transition metal oxides containing two or more transition metals have been developed to compensate for the problems of lithium transition metal oxides containing Ni, Co, or Mn alone, and among them, lithium nickel cobalt manganese oxides containing Ni, Co, and Mn are widely used in the field of electric vehicle batteries.

[0005] Conventional lithium nickel cobalt manganese oxides are generally in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles. However, in the case of lithium nickel cobalt manganese oxides in the form of secondary particles formed by agglomeration of many primary particles, there are problems in that particle cracking occurs easily when the primary particles fall off during the rolling process in the manufacture of the positive electrode, and cracks occur inside the particles during charging and discharging. When particle cracking or cracking occurs in the positive electrode active material, the contact area with the electrolyte increases, and gas generation and active material degradation due to side reactions with the electrolyte increase, resulting in a problem of reduced life characteristics.

[0006] Recently, the demand for high-output, high-capacity batteries, such as those for electric vehicles, has been increasing, and so the nickel content in the positive electrode active material has been gradually increasing. As the nickel content in the positive electrode active material increases, the initial capacity characteristics improve, but the highly reactive Ni +4 A large amount of ions are generated, causing the structure of the positive electrode active material to collapse, which increases the rate at which the positive electrode active material degrades, resulting in reduced life characteristics and reduced battery safety.

[0007] To solve the above problems, a technology has been proposed to manufacture a positive electrode active material in the form of a single particle rather than a secondary particle by increasing the sintering temperature during the manufacture of lithium nickel cobalt manganese oxide. In the case of a positive electrode active material in the form of a single particle, the contact area with the electrolyte is smaller than that of conventional positive electrode active materials in the form of secondary particles, so there are fewer side reactions with the electrolyte and the particle strength is excellent, so there is less particle cracking during electrode manufacture. Therefore, the use of a positive electrode active material in the form of a single particle has the advantage of excellent gas generation and life characteristics.

[0008] However, compared with conventional lithium composite transition metal oxide particles in the form of secondary particles, the size of the primary particles of the single-particle lithium composite transition metal oxide particles is relatively large, and there are few interfaces between the primary particles that serve as diffusion paths for lithium ions, resulting in reduced lithium mobility, and since they are manufactured at a relatively high sintering temperature, a rock salt phase is formed on the particle surface, resulting in high surface resistance. Therefore, the single-particle lithium composite transition metal oxide particles have a high lithium diffusion resistance, and lithium ions move non-uniformly during charging and discharging, which easily causes deformation of the crystal structure and particle cracks due to this, and the particle cracks increase resistance during charging and discharging, resulting in reduced life characteristics. Summary of the Invention [Problem to be solved by the invention]

[0009] In order to solve the above problems, the present invention aims to provide a single-particle or quasi-single-particle positive electrode active material having a small increase in resistance during charging and discharging and excellent capacity characteristics and life characteristics, a manufacturing method thereof, and a positive electrode and a lithium secondary battery using the positive electrode active material. [Means for solving the problem]

[0010] According to an embodiment, the present invention provides a positive electrode active material comprising: a lithium nickel-based oxide in the form of a quasi-single particle, which is a single particle consisting of one nodule or a composite of 30 or less nodules; and a coating portion containing Co formed in an island shape on a part of the surface of the lithium nickel-based oxide particle, the surface of the lithium nickel-based oxide in contact with the coating portion is measured by electron energy loss spectroscopy, and the intensity at 855.5 eV is greater than the intensity at 853 eV in a Ni L3-edge spectrum.

[0011] According to another embodiment, the present invention provides a method for preparing a positive electrode active material, the method including: mixing a transition metal precursor and a lithium source material, and calcining the mixture to prepare a lithium nickel-based oxide having a single particle or quasi-single particle form; and mixing the lithium nickel-based oxide with a cobalt-containing coating material, and then heat-treating the mixture at a temperature of 600°C to 750°C to form a coating portion.

[0012] According to still another embodiment, the present invention provides a positive electrode including a positive electrode active material layer including the positive electrode active material of the present invention, and a lithium secondary battery including the positive electrode. Effect of the Invention

[0013] The positive electrode active material according to the present invention includes a lithium nickel-based oxide in the form of a single particle or quasi-single particle having high particle strength, and has little particle cracking during the manufacture of the electrode and during charging and discharging. Since the contact area with the electrolyte is small, the occurrence of side reactions with the electrolyte is suppressed. Therefore, when used in a secondary battery, the amount of gas generation is small and the high-temperature life characteristics are excellent.

[0014] In addition, the positive electrode active material according to the present invention includes an island-shaped Co-containing coating portion on a part of the surface of a lithium nickel-based oxide particle, and more Ni ions having an oxidation number of +3 or more are present on the surface of the lithium nickel-based oxide particle in contact with the Co-containing coating portion, thereby minimizing an increase in resistance and improving capacity characteristics and life characteristics.

[0015] When a Co-containing coating portion is formed on the surface of lithium nickel-based oxide particles, the surface structure of the positive electrode active material is formed into a stable layer structure by Co, which facilitates the insertion and desorption of lithium ions, improves the surface stability of the positive electrode active material, and improves the initial capacity characteristics. However, if the Co-containing coating portion is formed in the form of a continuous film, although the surface stability is improved, there is a problem that the formation of an electrically inactive NiO rock-salt phase increases, resulting in an increase in resistance. Therefore, in the present invention, the Co coating conditions are controlled so that the Co-containing coating portion is formed in an island shape on a part of the surface of the lithium nickel-based oxide, and Ni is formed on the surface of the lithium nickel-based oxide in contact with the Co-containing coating portion. 2+ By suppressing the generation of ions, it is possible to improve the capacity and life characteristics while minimizing the increase in resistance.

[0016] Meanwhile, in the method for manufacturing a positive electrode active material according to the present invention, a lithium nickel-based oxide in the form of a single particle or quasi-single particle is manufactured, and then the lithium nickel-based oxide is mixed with a cobalt raw material and heat-treated at a specific temperature, so that the Co-containing coating portion is formed in an island shape, i.e., a shape in which particles are distributed sporadically, and the generation of a rock salt phase at the interface between the Co-containing coating portion and the lithium nickel-based oxide is suppressed, so that the oxidation number of nickel ions at the interface is +3 or more. [Brief description of the drawings]

[0017] [Figure 1] 2 shows a scanning electron microscope (SEM) image and an energy dispersive X-ray spectroscopy (EDS) Co-mapping image of the positive electrode active material prepared in Example 1. [Diagram 2] 1 shows an SEM image and an EDS Co mapping image of a positive electrode active material prepared in Example 2. [Diagram 3]1 shows an SEM image and an EDS Co mapping image of a positive electrode active material prepared in Example 3. [Figure 4] 1 shows an SEM image and an EDS Co mapping image of a positive electrode active material prepared according to Comparative Example 1. [Diagram 5] 1 shows an SEM image and an EDS Co mapping image of a positive electrode active material prepared according to Comparative Example 2. [Figure 6] 1 shows an SEM image and an EDS Co mapping image of a positive electrode active material prepared according to Comparative Example 3. [Figure 7] 2 shows a High-Angle Annular Dark-Field (HAADF) image and an Electron Energy Loss Spectroscopy (EELS) spectrum image of the positive electrode active material prepared in Example 1. [Figure 8] EELS Ni L3-edge spectra of regions 1 to 3 of the EELS spectrum image in Figure 7. [Figure 9] 2 shows an HAADF image and an EELS spectrum image of the positive electrode active material prepared according to Comparative Example 1. [Figure 10] EELS Ni L3-edge spectra of regions 1 and 2 of the EELS spectrum image in Figure 9. [Figure 11] 4 shows an HAADF image and an EELS spectrum image of the positive electrode active material prepared according to Comparative Example 2. [Figure 12] EELS Ni L3-edge spectra of regions 1 to 3 of the EELS spectrum image in FIG. 11. [Figure 13] 1 is a graph showing high-temperature life characteristics of secondary batteries to which the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 3 are applied. [Figure 14] 1 is a graph showing the resistance characteristics as a function of SOC of secondary batteries to which the positive electrode active materials of Examples 1 to 3 and Comparative Examples 1 to 3 are applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention will now be described in more detail.

[0019] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical ideas of the present invention, based on the principle that the inventor himself / herself can appropriately define the concepts of terms in order to explain the invention in the best possible way.

[0020] In the present invention, a "single particle" means a particle consisting of one nodule, and a "quasi-single particle" means a composite particle consisting of 30 or less nodules.

[0021] The "nodule" is a lower particle unit constituting a single particle or a quasi-single particle, and may be a single crystal having no crystalline grain boundary, or a polycrystal having no grain boundary when observed at a magnification of 5,000 to 20,000 using a scanning electron microscope.

[0022] In the present invention, the term "secondary particle" refers to a particle formed by agglomeration of a plurality of, for example, tens to hundreds of, primary particles. Specifically, the secondary particle may be an agglomeration of 50 or more primary particles.

[0023] In the present invention, the term "particle" is a concept including any one or all of a single particle, a quasi-single particle, a primary particle, a nodule, and a secondary particle.

[0024] In the present invention, the "average particle size D 50" means a particle size based on 50% of the volume cumulative particle size distribution of the lithium composite transition metal oxide powder or the positive electrode active material powder, and can be measured using a laser diffraction method. For example, the lithium composite transition metal oxide powder or the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and a volume cumulative particle size distribution graph is obtained, and the particle size corresponding to 50% of the volume cumulative amount is obtained.

[0025] In the present invention, the term "crystallite" refers to a particle unit having substantially the same crystal orientation, which can be identified through EBSD (Electron Backscatter Diffraction) analysis. Specifically, the crystallite is the smallest particle unit that is shown with the same color in an IPF map obtained by EBSD analysis of a cross section of a cathode active material cut by ion milling.

[0026] Meanwhile, in the present invention, the "average crystallite size" can be quantitatively analyzed using X-ray diffraction analysis (XRD) using Cu Kα X-rays. Specifically, the average crystallite size of the crystal grains can be quantitatively analyzed by placing the particles to be measured in a holder, irradiating the particles with X-rays, and analyzing the diffraction grating that emerges. Sampling was performed by placing a powder sample of the particles to be measured in a recessed groove in a general powder holder, leveling the surface using a slide glass, and preparing the sample height to be the same as the end of the holder. Then, X-ray diffraction analysis was performed using a Bruker D8 Endeavor (light source: Cu Kα, λ=1.54Å) equipped with a LynxEye XE-T position sensitive detector under the conditions of FDS0.5°, step size 0.02° for the 2θ=15°~90° region, and total scan time of about 20 minutes. The measured data was subjected to Rietveld refinement taking into account the charge at each site (metal ions at transition metal sites are +3, Ni ions at Li sites are +2) and cation mixing. When analyzing grain size, instrumental broadening was taken into account using the Fundamental Parameter Approach (FPA) implemented in the Bruker TOPAS program, and the entire peak in the measurement range was used during fitting. Peak shape was fitted using only the Lorenzian contribution in the First Principle (FP) peak type available in TOPAS, and strain was not considered in this case.

[0027] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.

[0028] positive electrode active material The positive electrode active material according to the present invention will be described below.

[0029] The positive electrode active material according to the present invention includes (1) lithium nickel-based oxide particles in the form of single particles or quasi-single particles, and (2) a Co-containing coating portion formed in an island shape on a part of the surface of the lithium nickel-based oxide particle.

[0030] (1) Lithium nickel oxide particles The lithium nickel-based oxide particle is a single particle consisting of one nodule, or a quasi-single particle which is a composite of 30 or less nodules, preferably 2 to 20 nodules, and more preferably 2 to 10 nodules.

[0031] Such lithium nickel-based oxide particles in the form of single particles or quasi-single particles have higher particle strength than existing lithium nickel-based oxide particles in the form of secondary particles in which tens to hundreds of primary particles are aggregated, and therefore are less susceptible to particle cracking during rolling.

[0032] In addition, in the case of the lithium nickel-based oxide in the form of a single particle or quasi-single particle according to the present invention, the number of nodules constituting the particle is small, so that there is little change due to the volume expansion and contraction of the nodules during charging and discharging, and therefore the occurrence of cracks inside the particles is significantly reduced.

[0033] Meanwhile, the lithium nickel-based oxide particles may have a composition in which the nickel content in all metals excluding lithium is 70 mol% or more, preferably 80 mol% or more, and more preferably 82 mol% or more, and more specifically, the lithium nickel cobalt manganese-based oxide may have a nickel content in all metals excluding lithium of 70 mol% or more, preferably 80 mol% or more, and more preferably 82 mol% or more. When the nickel content in the lithium nickel-based oxide particles satisfies the above range, a high energy density can be realized.

[0034] More specifically, the lithium nickel-based oxide particles may have a composition represented by the following [Chemical Formula 1].

[0035] [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O2

[0036] In the above formula 1, M 1 may be Mn, Al or a combination thereof, preferably Mn or Mn and Al.

[0037] Said M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Sr, Ti, Mg, Ta and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg and Ti, more preferably Zr, Y or a combination thereof. 2 Although the element is not essential, when contained in an appropriate amount, it can play a role in promoting grain growth during firing or improving the stability of the crystal structure.

[0038] The a represents the lithium molar ratio in the lithium nickel-based oxide, and may be 0.8≦a≦1.2, 0.85≦a≦1.15, or 0.9≦a≦1.2. When the lithium molar ratio satisfies the above range, the crystal structure of the lithium nickel-based oxide may be stably formed.

[0039] The b indicates a molar ratio of nickel in all metals other than lithium in the lithium nickel-based oxide, and may be 0.7≦b<1, 0.8≦b<1, or 0.82≦b<1. When the nickel molar ratio satisfies the above range, a high energy density can be exhibited, and a high capacity can be realized.

[0040] Said c represents the molar ratio of cobalt in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 < c < 0.3, 0 < c < 0.2, or 0.01 ≤ c ≤ 0.15. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.

[0041] Said d represents the molar ratio of element M in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 < d < 0.3, 0 < d < 0.2, or 0.01 ≤ d ≤ 0.15. 1 When the molar ratio of element M satisfies the above range, excellent structural stability of the positive electrode active material appears. 1 Said e represents the molar ratio of element M in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 ≤ e ≤ 0.2, 0 ≤ e ≤ 0.1, or 0 ≤ e ≤ 0.05.

[0042] 2

[0043] (2) Coating portion The positive electrode active material according to the present invention includes a coating portion containing Co, which is formed in an island shape on a part of the surface of the lithium nickel-based oxide particles in the form of single particles or quasi-single particles described above. Here, the island shape means a shape in which coating portions in the form of small particles are scattered on the surface of the lithium nickel-based oxide particles, and the coating portions in the form of particles may be spherical, plate-like, and / or amorphous.

[0044] ​​In the case of a high nickel-content positive electrode active material, there is a problem that the surface of the positive electrode active material where the positive electrode active material and the electrolyte come into contact with each other may experience a side reaction with the electrolyte, which may cause the elution of transition metals and structural collapse. In the past, in order to solve this problem, a method of coating the surface of a high nickel positive electrode active material with an oxide of a metal such as Al or boron to reduce contact with the electrolyte has been used. However, since such a coating layer is not electrically active, there is a problem that the resistance of the positive electrode active material increases when the coating layer is formed on the surface of the active material, and the increase in resistance becomes more severe as the thickness of the coating layer increases. In particular, in the case of a single particle or quasi-single particle positive electrode active material, the lithium diffusion resistance is higher than that of a conventional secondary particle type positive electrode active material, and therefore, when a conventional coating layer is applied to the surface of a single particle positive electrode active material, the problem of output reduction due to the increase in resistance occurs more seriously.

[0045] The present inventors have conducted extensive research to improve the resistance characteristics of a positive electrode active material having a single particle or quasi-single particle form, and have found that both the resistance characteristics and life characteristics can be improved by forming an island-shaped cobalt (Co)-containing coating portion on the surface of a lithium nickel-based oxide having a single particle or quasi-single particle form.

[0046] Since cobalt (Co) is an element advantageous for forming a layered structure, when the coating portion is formed using Co, the crystal structure on the surface of the positive electrode active material is stably formed, thereby reducing the lithium ion diffusion resistance, and suppressing the deformation of the crystal structure and the occurrence of particle cracks during charging and discharging, thereby improving the life characteristics. However, when the cobalt-containing coating portion is formed in the form of a continuous film on the surface of the lithium nickel-based oxide particles, the resistance increases again because the generation of the electrically inactive rock salt phase increases as Co diffuses on the surface of the lithium nickel-based oxide. Therefore, in the present invention, the heat treatment temperature is controlled during the formation of the coating portion so that the coating portion is formed in an island shape, thereby maximizing the improvement effect of the resistance characteristics and life characteristics. Specifically, the coating portion may be formed in an area of ​​10% to 60%, preferably 10% to 50%, of the total surface area of ​​the lithium nickel-based oxide particles. When the area of ​​the coating portion satisfies the above range, the improvement effect of the resistance characteristics and life characteristics is the most excellent.

[0047] Preferably, the coating part may be a particulate lithium cobalt oxide distributed sporadically on the surface of the lithium nickel-based oxide particles. The coating part according to the present invention is manufactured by mixing a cobalt-containing coating material with a lithium nickel-based oxide in the form of a single particle or quasi-single particle, followed by heat treatment, and lithium remaining on the surface of the lithium nickel-based oxide reacts with the cobalt of the coating material during the heat treatment to produce lithium cobalt oxide. When the residual lithium is removed by forming the coating part in this way, the water washing process for removing the residual lithium can be omitted, thereby simplifying the process. In addition, in general, during the water washing process, the Ni oxidation number on the surface of the positive electrode active material particles becomes electrically inactive Ni. 2+ Therefore, the resistance tends to increase, but if the water washing process is omitted, the change in the Ni oxidation number can be minimized, which has the effect of suppressing the increase in resistance.

[0048] Meanwhile, the lithium cobalt oxide may have a particle size of 100 nm to 1000 nm, preferably 300 nm to 700 nm, more preferably 400 nm to 600 nm. When the size of the coating particles satisfies the above range, the coating effectively suppresses the formation of an inactive rock salt phase on the surface of the lithium nickel oxide, resulting in excellent life performance at high temperatures.

[0049] Meanwhile, in the positive electrode active material of the present invention, the Ni L3-edge spectrum measured by electron energy loss spectroscopy on the surface of the lithium nickel-based oxide in contact with the coating portion has a higher intensity at 855.5 eV than the intensity at 853 eV.

[0050] Electron energy loss spectroscopy is a method for obtaining desired information such as the element, composition, and chemical bond state of a reaction site by measuring the energy loss of inelastic scattering electrons that occur when accelerated electrons react with a sufficiently thin specimen. Electron energy loss spectroscopy spectra can be divided into a low loss excitation region, which is a 0-50 eV energy loss portion, and a high loss region, which is a 50 eV or higher energy loss portion. In the high loss region, an ionization edge is shown, and the oxidation number of a metal can be analyzed using the ionization edge. In the present invention, Ni L3-edge spectrum was used to analyze the oxidation number of Ni. The EELS spectrum can be obtained using an HR-TEM device, and the horizontal axis indicates the loss energy region and the vertical axis indicates the peak intensity.

[0051] In the Ni L3-edge spectrum measured by EELS, 3+ The ion is shown at around 855.5 eV, Ni 2+The ions are shown at around 853 eV. Therefore, if the peak intensity at around 855.5 eV is large, it is Ni 3+ It means that there are many Ni ions. When the peak intensity around 853 eV is large, Ni 2+ In other words, the fact that the intensity at 855.5 eV is greater than the intensity at 853 eV in the Ni L3-edge spectrum indicates that there are many Ni ions in that region. 3+ This means that there are more ions, which indicates that the average oxidation number of nickel on the surface of the lithium nickel-based oxide in contact with the coating is +3 or more. When the average oxidation number of nickel on the coating and the surface of the lithium nickel oxide is high, such as +3 or more, the resistance is reduced, and the capacity and output characteristics are improved.

[0052] Specifically, in the positive electrode active material of the present invention, the intensity at 853 eV (I 853 ) vs. the intensity at 855.5 eV (I 855.5 ) ratio (I 855.5 / I 853 ) may be 1 to 3, preferably 1.2 to 3, and more preferably 1.5 to 3. I 855.5 / I 853 When the above range is satisfied, the resistance characteristics and life characteristics are particularly excellent.

[0053] On the other hand, in the positive electrode active material of the present invention, in the Ni L3-edge spectrum measured by electron energy loss spectroscopy on the surface of the lithium nickel-based oxide not covered with the coating portion, the intensity at 855.5 eV is preferably smaller than the intensity at 853 eV (i.e., the average oxidation number of nickel is less than +3).

[0054] Ni on the surface of the positive electrode active material 2+ The presence of a large amount of Ni ions has the advantage of reducing side reactions with the electrolyte. 2+ The problem is that the resistance increases because the ions are electrically inactive. 3+ Or Ni 4+ When nickel ions with a high oxidation number such as these are present on the surface of the positive electrode active material, excellent electrical properties such as capacity and output are exhibited. However, due to their high reactivity, side reactions with the electrolyte increase, accelerating the collapse of the structure of the positive electrode active material, and reducing the life characteristics.

[0055] However, as mentioned above, if the oxidation number of nickel is low on the surface not covered by the coating and high on the surface covered by the coating, the coating prevents contact between the highly reactive +3 or +4 valent nickel and the electrolyte, and the less reactive Ni is present in the area that comes into direct contact with the electrolyte. 2+ The arrangement of ions reduces resistance while minimizing side reactions with the electrolyte.

[0056] Meanwhile, the positive electrode active material according to the present invention may have an average particle size of nodules of 0.5 μm to 3 μm, preferably 0.8 μm to 2.5 μm, and more preferably 0.8 μm to 1.5 μm. When the average particle size of the nodules satisfies the above range, a positive electrode active material having a single particle or quasi-single particle form with excellent electrochemical properties can be formed. When the average particle size of the nodules is very small, the number of agglomerates of particles forming the lithium nickel-based oxide particles increases, and the effect of suppressing particle breakage during rolling decreases. When the average particle size of the nodules is very large, the lithium diffusion path inside the particles becomes long, increasing resistance and possibly decreasing output characteristics.

[0057] The positive electrode active material has an average particle size D 50 The diameter of the positive electrode active material may be 2 μm to 6 μm, preferably 2 μm to 5 μm, and more preferably 3 μm to 5 μm. 50 If the D is very small, it is difficult to form an active material layer during electrode production, and the electrolyte impregnation property decreases, resulting in a decrease in electrochemical properties. 50 If the resistance is too large, the resistance increases and the output characteristics deteriorate.

[0058] In addition, the positive electrode active material may have an average crystallite size of 150 nm to 300 nm, 200 nm to 280 nm, or 200 nm to 250 nm. When the average crystallite size is within this range, the formation of a rock salt phase during the preparation of a lithium nickel-based oxide is reduced, and a positive electrode active material in the form of a single particle or quasi-single particle with excellent resistance characteristics can be prepared. Generally, a positive electrode active material in the form of a single particle or quasi-single particle is prepared by increasing the sintering temperature to increase the size of the nodules. However, if the size of the nodules is increased while the crystallite size is small, a rock salt phase is formed on the surface of the nodules, which increases the resistance. However, if both the average crystallite size and the average particle size of the nodules are increased, the formation of the rock salt phase is minimized, and an effect of suppressing an increase in resistance can be obtained.

[0059] Method for producing positive electrode active material Next, a method for producing the positive electrode active material according to the present invention will be described.

[0060] The method for producing a positive electrode active material according to the present invention includes the steps of (1) mixing a transition metal precursor and a lithium source material, and sintering the mixture to produce a lithium nickel-based oxide in a single particle or quasi-single particle form, and (2) mixing the lithium nickel-based oxide with a cobalt-containing coating material, and then heat-treating the mixture at a temperature of 600°C to 750°C to form a coating portion.

[0061] (1) The manufacturing stage of lithium nickel oxide First, a transition metal precursor and a lithium source material are mixed and primarily sintered to prepare a lithium nickel-based oxide in the form of a single particle or a similar single particle.

[0062] In this case, the transition metal precursor may be a commercially available precursor such as nickel-cobalt-manganese hydroxide, or may be prepared by a method known in the art.

[0063] Preferably, the transition metal precursor used in the present invention may be a transition metal hydroxide containing nickel and cobalt, with the Ni content of the total transition metal being 80 mol% or more, more preferably a nickel cobalt manganese hydroxide with the Ni content being 80 mol% or more. When the nickel content in the transition metal precursor satisfies the above range, high capacity characteristics can be realized.

[0064] Specifically, the transition metal precursor may have a composition represented by the following [Chemical Formula 2].

[0065] [Chemical formula 2] Ni x Co y M 1 z M 2 w (OH)2 In the above formula 2, M 1 is Mn, Al or a combination thereof, preferably Mn or a combination of Mn and Al.

[0066] The above-mentioned M 2 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Sr, Ti, Mg, Ta, and Nb, preferably one or more selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof.

[0067] The above-mentioned x represents the molar ratio of nickel in all the metals in the precursor, and may be 0.8 ≦ x < 1, 0.82 ≦ x < 1, or 0.83 ≦ x < 1. When the molar ratio of nickel satisfies the above range, it exhibits a high energy density and enables the realization of a high capacity.

[0068] The above-mentioned y represents the molar ratio of cobalt in all the metals in the precursor, and may be 0 < y < 0.2, 0 < y < 0.18, or 0.01 ≦ y ≦ 0.17. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.

[0069] The above-mentioned z represents the molar ratio of the M 1 element in all the metals in the precursor, and may be 0 < z < 0.2, 0 < z < 0.18, or 0.01 ≦ z ≦ 0.17. When the molar ratio of the M 1 element satisfies the above range, excellent structural stability of the positive electrode active material appears.

[0070] The above-mentioned w represents the molar ratio of the M 2 element in all the metals in the precursor, and may be 0 ≦ w ≦ 0.1 or 0 ≦ w ≦ 0.05.

[0071] For example, the above-mentioned transition metal precursor may be produced by introducing a transition metal aqueous solution, an ammonium cation complex-forming agent, and a basic compound into a reactor and stirring while allowing a coprecipitation reaction to proceed.

[0072] The above-mentioned transition metal aqueous solution can be produced by dissolving a transition metal-containing raw material substance in a solvent such as water. For example, a nickel-containing raw material substance and a cobalt-containing raw material substance can be dissolved in water for production. Also, if necessary, the above-mentioned transition metal aqueous solution may contain M1 Raw material and / or M 2 It may further include a metal-containing source material.

[0073] Meanwhile, the transition metal-containing source material may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, or oxide of a transition metal.

[0074] Specifically, the nickel-containing source material may be, for example, NiO, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, nickel halides, or combinations thereof.

[0075] The cobalt-containing source material can be, for example, CoSO4, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4·7H2O, or combinations thereof.

[0076] Said M 1 The containing raw material may be a manganese-containing raw material and / or an aluminum-containing raw material. The manganese-containing raw material may be, for example, Mn2O3, MnO2, Mn3O4MnCO3, Mn(NO3)2, MnSO4·H2O, manganese acetate, manganese halide, or a combination thereof, and the aluminum-containing raw material may be, for example, Al2O3, Al(OH)3, Al(NO3)3, Al2(SO4)3, (HO)2AlCH3CO2, HOAl(CH3CO2)2, Al(CH3CO2)3, aluminum halide, or a combination thereof. However, in the case of Al, it does not matter if it is not added to the transition metal aqueous solution but is added together with the lithium raw material in the firing step described below.

[0077] M 2 The raw materials contained are M 2 The metal may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, or oxide.

[0078] The amount of each of the transition metal-containing raw materials to be added may be determined in consideration of the molar ratio of the transition metal in the final cathode active material to be produced.

[0079] Meanwhile, the ammonium cation complexing agent may include at least one compound selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and (NH4)2CO3, and may be added to the reactor in the form of a solution in which the compound is dissolved in a solvent. In this case, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water.

[0080] The basic compound may be at least one compound selected from the group consisting of NaOH, KOH, and Ca(OH)2, and may be added to the reactor in the form of a solution in which the compound is dissolved in a solvent. In this case, the solvent may be water or a mixture of water and an organic solvent (e.g., alcohol) that is uniformly miscible with water.

[0081] When the aqueous transition metal solution, the ammonium cation complex former, and the basic compound are charged into a reactor and stirred as described above, the transition metal in the aqueous transition metal solution is coprecipitated to produce precursor particles in the form of transition metal hydroxide.

[0082] In this case, the transition metal aqueous solution, the ammonium cation complex forming agent, and the basic compound are added in amounts such that the pH of the reaction solution falls within a desired range.

[0083] When the precursor particles are formed by the above method, the particles are separated from the reaction solution to obtain the transition metal precursor. For example, the reaction solution is filtered to separate the transition metal precursor from the reaction solution, and the separated transition metal precursor is washed with water and dried to obtain the transition metal precursor. In this case, a process such as pulverization and / or distribution may be performed as necessary.

[0084] Next, the transition metal precursor and the lithium source material are mixed and then sintered to prepare a lithium nickel-based oxide in the form of a single particle or a similar single particle. 1 Contains raw materials and / or M 2 The raw materials may be mixed together and fired; 1 Contains raw materials and / or M 2 Specific examples of the raw materials contained are as described above.

[0085] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, for example, Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, Li3C6H5O7, or a mixture thereof.

[0086] Meanwhile, the lithium source material and the positive electrode active material precursor may be mixed so that the molar ratio of Li:total metals in the precursor is 1:1 to 1.1:1, preferably 1.02:1 to 1.05:1. When the mixing ratio of the lithium source material and the metals in the positive electrode active material precursor satisfies the above range, the layered crystal structure of the positive electrode active material is developed, and a positive electrode active material having excellent capacity characteristics and structural stability can be produced.

[0087] Meanwhile, the calcination is performed at a temperature capable of forming single particles or quasi-single particles. In order to form single particles or quasi-single particles, the calcination should be performed at a higher temperature than that in the preparation of conventional lithium nickel-based oxide in the form of secondary particles. For example, when the precursor composition is the same, the calcination should be performed at a temperature about 30°C to 100°C higher than that in the preparation of conventional lithium nickel-based oxide in the form of secondary particles. The calcination temperature for forming single particles or quasi-single particles may vary depending on the metal composition in the precursor. For example, when a high-nickel (High-Ni) lithium nickel-based oxide having a nickel (Ni) content of 80 mol% or more is to be formed as single particles or quasi-single particles, the calcination temperature may be about 800°C to 1000°C, preferably 800°C to 950°C, and more preferably 850°C to 950°C. When the calcination temperature satisfies the above range, a lithium nickel-based oxide in the form of single particles or quasi-single particles having excellent electrochemical properties may be prepared. If the sintering temperature is less than 800° C., a positive electrode active material in the form of secondary particles is produced, and if the sintering temperature exceeds 1000° C., excessive sintering occurs, a layered crystal structure is formed, and the electrochemical properties are deteriorated.

[0088] The firing may be performed in an oxygen atmosphere for 5 to 35 hours, preferably 5 to 20 hours, and more preferably 6 to 15 hours. In this specification, the oxygen atmosphere means an atmosphere containing sufficient oxygen for firing, including the air atmosphere. In particular, it is preferable to perform the firing in an atmosphere having a higher oxygen partial pressure than the air atmosphere.

[0089] The lithium nickel-based oxide produced by the above-mentioned firing has a quasi-single particle form that is a single particle consisting of one nodule, or a composite of 30 or less, preferably 2 to 20, and more preferably 2 to 10 nodules.

[0090] In addition, the lithium nickel-based oxide particles may have a composition in which the nickel content in all metals excluding lithium is 80 mol% or more, preferably 82 mol% or more, and more preferably 83 mol% or more, and more specifically, the lithium nickel cobalt manganese-based oxide may have a nickel content in all metals excluding lithium of 80 mol% or more, preferably 82 mol% or more, and more preferably 83 mol% or more. When the nickel content in the lithium nickel-based oxide particles satisfies the above range, a high energy density can be realized.

[0091] More specifically, the lithium nickel-based oxide particles may have a composition represented by the following [Chemical Formula 1].

[0092] [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O2

[0093] In the above formula 1, M 1 may be Mn, Al or a combination thereof, preferably Mn or Mn and Al.

[0094] Said M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Sr, Ti, Mg, Ta and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg and Ti, more preferably Zr, Y or a combination thereof. 2 Although the element is not essential, when contained in an appropriate amount, it can play a role in promoting grain growth during firing or improving the stability of the crystal structure.

[0095] Said a represents the molar ratio of lithium in the lithium nickel-based oxide, and may be 0.8 ≦ a ≦ 1.2, 0.85 ≦ a ≦ 1.15, or 0.9 ≦ a ≦ 1.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium nickel-based oxide can be stably formed.

[0096] Said b represents the molar ratio of nickel in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0.8 ≦ b < 1, 0.82 ≦ b < 1, or 0.83 ≦ b < 1. When the molar ratio of nickel satisfies the above range, it shows a high energy density and enables the realization of a high capacity.

[0097] Said c represents the cobalt molar ratio in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 < c < 0.2, 0 < c < 0.18, or 0.01 ≦ c ≦ 0.17. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.

[0098] Said d represents the molar ratio of the M 1 element in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 < d < 0.2, 0 < d < 0.18, or 0.01 ≦ d ≦ 0.17. When the molar ratio of the M 1 element satisfies the above range, the structural stability of the positive electrode active material is excellently manifested.

[0099] Said e represents the molar ratio of the M 2 element in all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 ≦ e ≦ 0.1, or 0 ≦ e ≦ 0.05.

[0100] (2) Coating part formation stage Next, after mixing the lithium nickel-based oxide in the single particle or quasi-single particle form and the cobalt-containing coating substance, heat treatment is performed to form a coating part.

[0101] The cobalt-containing coating material may be, for example, one or more selected from the group consisting of Co3O4, Co(OH)2, Co2O3, Co3(PO4)2, CoF3, Co(OCOCH3)2·4H2O, Co(NO3)·6H2O, Co(SO4)2·7H2O and CoC2O4, preferably one or more selected from Co3O4 and Co(OH)2, more preferably Co(OH)2, but is not limited thereto.

[0102] The average particle size of the cobalt-containing coating raw material may be 100 nm to 1000 nm, preferably 300 nm to 700 nm, and more preferably 400 nm to 600 nm. When the average particle size of the cobalt-containing coating raw material satisfies the above range, it can be smoothly coated on the surface of the lithium nickel-based oxide, and the formation of a rock salt phase at the interface between the coating portion and the lithium nickel-based oxide is suppressed, resulting in an excellent effect of improving resistance characteristics.

[0103] Meanwhile, the lithium nickel-based oxide and the cobalt-containing coating material may be mixed in a solid phase or a liquid phase. However, in the case of liquid phase mixing, the process is complicated and the lithium nickel-based oxide may be damaged by the solvent during the coating process. Therefore, it is more preferable to mix them through solid phase mixing.

[0104] In addition, the lithium nickel-based oxide and the cobalt-containing coating material may be mixed in a weight ratio of 100:1 to 100:8, preferably 100:1 to 100:6, and more preferably 100:2 to 100:5. When the mixing ratio of the lithium nickel-based oxide and the cobalt-containing coating material satisfies the above range, the nickel content in the positive electrode active material can be secured to a certain level, and the amount of expensive cobalt raw material used can be reduced, thereby saving costs and effectively suppressing an increase in resistance.

[0105] Meanwhile, the heat treatment is preferably carried out in a temperature range of 600° C. to 750° C., preferably 600° C. to 700° C., and more preferably 650° C. to 700° C. When the heat treatment temperature during the formation of the coating layer satisfies the above range, the Co-containing coating portion suppresses the formation of a rock salt phase at the interface between the Co-containing coating portion and the lithium nickel-based oxide, and the coating portion is formed in an island shape on part of the surface of the lithium nickel-based oxide.

[0106] Meanwhile, the method for producing the positive electrode active material according to the present invention preferably does not include a washing step. Conventionally, when producing a high-nickel (High-Ni) NCM-based lithium nickel-based oxide having a nickel (Ni) content of 80 mol% or more, a washing step is generally performed after calcination in order to reduce the lithium by-product content. However, according to the research of the present inventors, it has been shown that if a washing step is performed during the production of a positive electrode active material in the form of a single particle or quasi-single particle, the surface characteristics of the lithium nickel-based oxide are deteriorated during the washing process, and the resistance is increased. Therefore, when producing the positive electrode active material according to the present invention, washing is not performed, and the residual lithium on the surface of the lithium nickel-based oxide is consumed through a coating part formation process, which is more effective in improving the resistance characteristics.

[0107] positive electrode Next, the positive electrode according to the present invention will be described.

[0108] The positive electrode according to the present invention includes a positive electrode active material layer including the positive electrode active material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material according to the present invention. The positive electrode active material has been described above, so the remaining components will be described below.

[0109] In the positive electrode, the positive electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the positive electrode current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0110] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.

[0111] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.

[0112] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the positive electrode active material layer.

[0113] The positive electrode may be manufactured by a conventional method for manufacturing a positive electrode. For example, the positive electrode may be manufactured by mixing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, applying the positive electrode slurry onto a positive electrode current collector, and then drying and rolling the positive electrode slurry. In this case, the types and contents of the positive electrode active material, binder, and conductive material are as described above.

[0114] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to have a viscosity that allows excellent thickness uniformity when the slurry is applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.

[0115] Alternatively, the positive electrode may be manufactured by casting the positive electrode slurry on a separate support, peeling the positive electrode slurry from the support, and laminating the resulting film on a positive electrode current collector.

[0116] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.

[0117] The lithium secondary battery of the present invention includes the positive electrode according to the present invention. Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, and the positive electrode is as described above. In addition, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0118] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0119] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 to 500 μm, and may have fine irregularities formed on the surface of the current collector to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0120] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0121] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, among which any one or a mixture of two or more may be used.

[0122] Also, a metallic lithium thin film may be used as the negative electrode active material. Also, as the carbon material, both low crystalline carbon and high crystalline carbon may be used. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0123] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing a chemical change in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and carbon nanotubes; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be usually contained in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.

[0124] The binder serves to improve the adhesion between the negative electrode active material particles and the adhesive strength between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight, based on the total weight of the negative electrode active material layer.

[0125] For example, the negative electrode active material layer may be manufactured by coating a negative electrode slurry including a negative electrode active material and, optionally, a binder and a conductive material on a negative electrode current collector and drying the coated negative electrode slurry, or by casting the negative electrode slurry on a separate support and then peeling the negative electrode slurry from the support to obtain a film, which may then be laminated on the negative electrode current collector.

[0126] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0127] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0128] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0129] The organic solvent may be any organic solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, or the like; dibutyl ether; ether-based solvents such as ether or tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; carbonate-based solvents such as dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylenecarbonate (EC), and propylenecarbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a C2 to C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes. Among these, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of the battery, and low-viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred.

[0130] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within a range of 0.1 to 5.0M, and more preferably 0.1 to 3.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore excellent electrolyte performance can be exhibited, and lithium ions can be effectively transferred.

[0131] In addition to the constituents of the electrolyte, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, improving the discharge capacity of the battery, etc. For example, the additives may be haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination, but are not limited thereto. The additives may be contained in an amount of 0.1% by weight to 10% by weight, preferably 0.1% by weight to 5% by weight, based on the total weight of the electrolyte.

[0132] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0133] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0134] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0135] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the exemplary embodiments set forth herein.

[0136] Manufacturing Example 1 Transition metal precursor Ni 0.86 Co 0.08 Mn 0.06 (OH)2 and LiOH·H2O were added to a 700 L Henschel mixer so that the weight ratio of transition metals (Ni+Co+Mn):Li was 1:1.05, and mixed at 400 rpm for 20 minutes. The mixed powder was placed in an alumina crucible measuring 330 mm x 330 mm and sintered at 890°C for 12 hours in an oxygen (O2) atmosphere to obtain lithium nickel oxide Li[Ni 0.86 Co 0.08 Mn 0.06 ]O2 was produced.

[0137] Manufacturing Example 2 Transition metal precursor Ni 0.93 Co 0.05 Mn 0.02(OH)2 and LiOH·H2O were added to a 700 L Henschel mixer so that the weight ratio of transition metals (Ni+Co+Mn):Li was 1:1.05, and mixed at 400 rpm for 20 minutes. The mixed powder was placed in an alumina crucible measuring 330 mm x 330 mm and sintered at 855°C for 15 hours in an oxygen (O2) atmosphere to obtain lithium nickel oxide Li[Ni 0.93 Co 0.05 Mn 0.02 ]O2 was produced.

[0138] Example 1 The lithium nickel-based oxide prepared in Preparation Example 1 and Co(OH)2 were mixed in a weight ratio of 100:3 and heat-treated at 700°C for 5 hours to prepare a positive electrode active material having a Co-containing coating portion formed on the surface of the lithium nickel-based oxide in the form of single particles or quasi-single particles.

[0139] Example 2 The lithium nickel-based oxide prepared in Preparation Example 1 and Co(OH)2 were mixed in a weight ratio of 100:1.5 and heat-treated at 700°C for 5 hours to prepare a positive electrode active material having a Co-containing coating portion formed on the surface of the lithium nickel-based oxide in the form of single particles or quasi-single particles.

[0140] Example 3 The lithium nickel-based oxide prepared in Preparation Example 2 and Co(OH)2 were mixed in a weight ratio of 100:2 and heat-treated at 660°C for 5 hours to prepare a positive electrode active material having a Co-containing coating portion formed on the surface of the lithium nickel-based oxide in the form of single particles or quasi-single particles.

[0141] Comparative Example 1 The lithium nickel-based oxide prepared in Preparation Example 1 and Co(OH)2 were mixed in a weight ratio of 100:3 and heat-treated at 800°C for 5 hours to prepare a positive electrode active material having a Co-containing coating portion formed on the surface of the lithium nickel-based oxide in the form of single particle or quasi-single particle.

[0142] Comparative Example 2 The lithium nickel-based oxide prepared in Preparation Example 1 was used as a positive electrode active material.

[0143] Comparative Example 3 The lithium nickel-based oxide prepared in Preparation Example 2 and Co(OH)2 were mixed in a weight ratio of 100:2 and heat-treated at 800°C for 5 hours to prepare a positive electrode active material having a Co-containing coating portion formed on the surface of the lithium nickel-based oxide in the form of single particles or quasi-single particles.

[0144] Experimental example 1: Confirmation of the coating shape The particle morphology and the shape of the coating portion of the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were observed through SEM and EDS analysis. Figures 1 to 6 show the SEM and EDS analysis results of the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, respectively.

[0145] 1 to 6, it can be seen that the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 contain lithium nickel-based oxide in a quasi-single particle form, which is a complex of 10 or less nodules.

[0146] 1 to 6, it can be seen that the positive electrode active materials prepared in Examples 1 to 3 are coated with island-like small micrometer-sized particles containing Co sporadically on a part of the surface of the quasi-single particle lithium nickel-based oxide. The area of ​​the coated portion is about 20% or less of the total surface area of ​​the lithium nickel-based oxide particles.

[0147] Meanwhile, referring to FIGS. 4 and 6, it can be seen that the positive electrode active materials prepared according to Comparative Examples 1 and 3 have a continuous film-like Co-containing coating portion formed on the surface of the quasi-single particle lithium nickel-based oxide.

[0148] Also, referring to FIG. 5, it can be seen that in the positive active material of Comparative Example 2, no Co-containing coating portion is present on the surface of the quasi-single particle lithium nickel-based oxide.

[0149] Experimental Example 2 EELS (Electron Energy Loss Spectroscopy) analysis was performed on the interface between the surface of the lithium nickel oxide and the coating portion of each of the positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 to obtain Ni L3-edge spectra, and the ratio of the intensity at 855.5 eV to the intensity at 853 eV in the spectra was calculated as I 855.5 / I 853 The measurement results are shown in Table 1 below.

[0150] [Table 1]

[0151] 7 to 11 show High-Angle Annular Dark-Field (HAADF) images and Electron Energy Loss Spectroscopy (EELS) spectrum images of the positive electrode active materials prepared in Example 1 and Comparative Examples 1 and 2.

[0152] FIG. 7 shows a High-Angle Annular Dark-Field (HAADF) image and an Electron Energy Loss Spectroscopy (EELS) spectrum image of the positive electrode active material prepared in Example 1, and FIG. 8 shows an EELS Ni L3-edge spectrum of regions 1 to 3 of the EELS spectrum image of FIG. 7.

[0153] FIG. 9 shows an HAADF image and an EELS spectrum image of the positive electrode active material prepared according to Comparative Example 1, and FIG. 10 shows an EELS Ni L3-edge spectrum of regions 1 and 2 of the EELS spectrum image of FIG.

[0154] FIG. 11 shows an HAADF image and an EELS spectrum image of the positive electrode active material prepared according to Comparative Example 2, and FIG. 12 shows an EELS Ni L3-edge spectrum of regions 1 to 3 of the EELS spectrum image of FIG.

[0155] 7 and 8, in the case of the positive electrode active material prepared according to Example 1, it can be seen that the intensity at 855.5 eV is greater than the intensity at 853 eV in the EELS Ni L3-edge spectrum of region 3, which is the surface of the lithium nickel-based oxide in contact with the Co coating, and the EELS spectrum image shows that the nickel oxidation number in region 3 is high at +3 or more. In contrast, the intensity at 855.5 eV is less than the intensity at 853 eV in the EELS Ni L3-edge spectrum of region 1, where no coating is present, and the EELS spectrum image also shows that the nickel oxidation number in region 3 is low at less than +3.

[0156] Meanwhile, referring to FIGS. 9 and 10, in the case of the cathode active material of Comparative Example 1 in which a Co-containing coating portion is formed on the entire surface of the lithium nickel-based oxide, the EELS Ni L3-edge spectrum of Region 1, which is the interface between the coating portion and the lithium nickel-based oxide, shows similar intensities at 855.5 eV and 853 eV, and it can be seen that the nickel oxidation number in Region 1 in the EELS spectrum image is low, being less than +3.

[0157] In addition, referring to FIGS. 11 and 12, in the case of the positive electrode active material of Comparative Example 2 in which the Co coating portion is not formed, Ni with a low oxidation number, i.e., a valence of +2, is distributed over the entire surface of the lithium nickel-based oxide.

[0158] <Secondary battery manufacturing> The positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3, the carbon black conductive material, and the PVDF binder were mixed in a weight ratio of 95:2:3 in N-methylpyrrolidone to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, dried at 130°C, and rolled to prepare positive electrodes.

[0159] A lithium metal electrode was used as the negative electrode.

[0160] A separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case, and an electrolyte was injected into the case to prepare a lithium secondary battery. The electrolyte was prepared by dissolving LiPF6 at a concentration of 1M in a mixed organic solvent in which ethylene carbonate / dimethyl carbonate / diethyl carbonate were mixed in a volume ratio of 3:4:3.

[0161] Experimental example 3: Evaluation of initial charge and discharge The initial charge / discharge capacity was measured by charging each of the lithium secondary batteries prepared above to 4.25 V in CC-CV mode and then discharging to 2.5 V in CC mode. In this case, the lithium secondary batteries using the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2 were charged and discharged at a 0.1 C rate, and the lithium secondary batteries using the positive electrode active materials of Example 3 and Comparative Example 3 were charged and discharged at a 0.2 C rate.

[0162] Experimental example 4: Evaluation of 45℃ cycle characteristics Each of the lithium secondary batteries prepared above was charged at 45° C. in CC-CV mode at 0.5 C until it reached 4.3 V, and then discharged at a constant current of 1.0 C until it reached 2.5 V, which constituted one cycle. After 50 cycles of charge and discharge, the capacity retention rate and the resistance increase rate were measured to evaluate the life characteristics. The measurement results are shown in Table 2 below and FIG. 13.

[0163] [Table 2]

[0164] From Table 2 and FIG. 13, it can be seen that the lithium secondary batteries using the positive electrode active materials of Examples 1 to 3 have superior initial charge / discharge capacity and life characteristics compared to the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 to 3, and in particular, the resistance increase rate is significantly reduced.

[0165] Experimental example 5: Evaluation of resistance characteristics by SOC Each of the lithium secondary batteries prepared above was charged and discharged once at 0.2C / 0.2C, and then each SOC state was set at 0.2C, and a current of 2.5C was applied for 10 seconds, and the resistance was measured based on the change in voltage when a current of 2.5C was applied. The measurement results are shown in FIG.

[0166] From FIG. 14, it can be seen that the lithium secondary battery employing the positive electrode active material of the example in which the Co coating portion is formed in an island shape on a part of the surface of the lithium nickel-based oxide particle and the Ni L3-edge spectrum on the surface of the lithium nickel-based oxide particle in contact with the coating portion satisfies the conditions of the present invention has lower resistance characteristics than the lithium secondary battery employing the positive electrode active material of the comparative example.

Claims

1. A lithium nickel-based oxide having a quasi-single particle form, which is a single particle consisting of one nodule or a composite of 30 or less nodules; A coating portion containing Co, which is formed in an island shape on a part of the surface of the lithium nickel-based oxide particle, A positive electrode active material in which an intensity at 855.5 eV is greater than an intensity at 853 eV in a Ni L3-edge spectrum obtained by measuring a surface of the lithium nickel-based oxide in contact with the coating portion by electron energy loss spectroscopy.

2. 2. The positive electrode active material according to claim 1, wherein a Ni L3-edge spectrum obtained by measuring a surface of the lithium nickel-based oxide on which the coating portion is not formed by electron energy loss spectroscopy has an intensity at 855.5 eV lower than an intensity at 853 eV.

3. The positive electrode active material according to claim 1 , wherein the coating portion is formed over an area of ​​10% to 60% of the total surface area of ​​the lithium nickel-based oxide particles.

4. The positive electrode active material of claim 1 , wherein the coating portion is formed of particulate lithium cobalt oxide distributed sporadically.

5. The positive electrode active material according to claim 4, wherein the lithium cobalt oxide has a particle size of 100 nm to 1000 nm.

6. The positive electrode active material according to claim 1, wherein the lithium nickel-based oxide has a composition represented by the following [Chemical Formula 1]: [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O 2 In Formula 1, M 1 is Mn, Al or a combination thereof, M 2 are Zr, W, Ti, Mg, Ca, Sr, and Ba, and 0.8≦a≦1.2, 0.83≦b<1, 0<c<0.17, 0<d<0.17, and 0≦e≦0.

1.

7. mixing a transition metal precursor and a lithium source material and calcining the mixture to prepare a lithium nickel-based oxide having a single particle or quasi-single particle form; and mixing the lithium nickel-based oxide with a cobalt-containing coating material, and then heat-treating the mixture at a temperature of 600° C. to 750° C. to form a coating portion.

8. The cobalt-containing coating material is Co 3 O 4 , Co(OH) 2 , Co 2 O 3 , Co 3 (P.O. 4 ) 2 , CoF 3 , Co(OCOCH 3 ) 2 ・4H 2 O, Co(NO 3 ) 6H 2 O, Co(SO 4 ) 2 ・7H 2 O and CoC 2 O 4 The method for producing a positive electrode active material according to claim 7, wherein the positive electrode active material is one or more selected from the group consisting of:

9. The method of claim 7, wherein the cobalt-containing coating material has an average particle size of 100 nm to 1000 nm.

10. 8. The method of claim 7, wherein the lithium nickel-based oxide and the cobalt-containing coating material are mixed in a weight ratio of 100:1 to 100:

8.

11. The method for producing a positive electrode active material according to claim 7 , wherein the transition metal precursor is a nickel-cobalt-manganese hydroxide having a Ni content of 80 mol % or more.

12. The method of claim 7 , wherein the forming of the coating portion is performed without a water washing process after the preparing of the lithium nickel-based oxide.

13. A positive electrode comprising a positive electrode active material layer comprising the positive electrode active material according to claim 1 .

14. A lithium secondary battery comprising the positive electrode according to claim 13.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, method for producing the same, positive electrode for lithium secondary battery containing the same, and lithium secondary battery

    JP2020525993A